Behavior of C70 Fullerene in a Binary Mixture of Xylene and Tetrahydrofuran - Urol K. Makhmanov; Shaxboz A. Esanov; Dostonbek T. Sidigaliyev; Kayyum N. Musurmonov; Bobirjon A. Aslonov; Tohirjon A. Chuliev (Liquids, 2023)
The self-organization properties of C70 fullerene molecules in a xylene/tetrahydrofuran binary mixture were studied for the first time by optical absorption, refractometry, and dynamic light scattering. A correlation has been established between the change in the refractive index of the C70/xylene/tetrahydrofuran solution and the degree of self-organization of C70 molecules in the medium at various concentrations and storage periods of the solution. It is shown that the features of the optical absorption spectrum of C70/xylene/tetrahydrofuran at a fixed low concentration of fullerene are sensitive to its storage time. It was determined that the beginning time of the formation of C70 nanoclusters and their final size depend on the degree of concentration of fullerene and the time spent keeping the solution. The observed nature of the C70 fullerene solution in a binary mixture may help to elucidate its mechanism of self-organization in the future.